Partially Funded Pension, Fertility and Endogenous Growth - Yang, Zaigui (Assurances et gestion des risques / Insurance and Risk Management, 2007)
Within a framework of an overlapping generations endogenous growth model, this paper examines the effects of China’s partially funded public pension on fertility, economic growth and family old-age security. Chinese are assumed to satisfy for both having children and getting old-age material support from children. It is shown that raising the firm contribution rate reduces the rates of fertility and intergenerational transfer, and increases the economic growth rate. The individual contribution has no effect on the above rates. This paper also finds the proper firm contribution rate interval to promote economic growth, control population rationally and maintain some family old-age security.